Methodology identification in mass disasters - Ampudia García, Omar (2012)
Major disasters in Perul ack from a treatment plan and adapt to the current reality. Were rare and limited to natural disasters such as major earthquakes, floods, torrential rains, erupting volcanoes, and so on.At first these disasters were limited to certain geographic areas ingeneral,but with the advancement of science and technology these events have soared alarming lyas rail crashes, plane crashes, car crashes going at high speed,and if we add the attacks by fundamentalist groups with car bomb sorthe Twin Towers. These factshave a common denominator,a high accident rate and material losses for a country. In order toprovide an effective response to disasters and plannedmassis that itanalyzes the performance of different methodologies Interpol protocol, the Ministryof Justice of the United States and the Spanish BOE.